The number of insects of midges complex and ratio of its various components in the forest-steppe zone of the Tyumen Region - T. A. Khlyzova (Российский паразитологический журнал)
The purpose of the research is comparing abundance levels of blood-sucking dipterans in the forest-steppe zone of the Tyumen Region for 8 years with different meteorological conditions.Materials and methods. The studies were carried out in 2006 and 2013–2019 in vicinity of the villages of Isetskoe and Barkhatovo, Isetsky District, Tyumen Region. Tabanid flies were collected and counted using funnel-shaped traps permanently on the same pasture on a regular basis once every 5–7 days during the entire emergence period. When counting the number of mosquitoes, midges and sandflies, we used a net with removable bags. Each count included 10 sweeps with a motion of the figure eight "around itself" in 10 replications.Results and discussion. The abundance of blood-sucking dipterans is largely determined by natural and climatic conditions and a hydrological regime of rivers, and is liable to significant fluctuations. The maximum abundance of gnats was recorded in 2014, the minimum in 2006. In comparing the average number for seasons with maximum and minimum abundance, a difference of 3.7 times was found. The abundance level and ratio of individual components of the midges complex depending on the season also underwent significant changes. In collected insects, midges dominated in 2006 and 2014, and mosquitoes in 2013 and in 2015–2019. Meteorological and hydrological conditions in winter and spring had the biggest impact on the abundance level of insects of the midges complex. Fluctuations in the abundance were 9 times for mosquitoes, 20 times for tabanid flies, and 39 times for midges and sandflies depending on the season. The main limiting factors for mass development of blood-sucking Diptera in the forest-steppe zone of the Tyumen Region are hard and dry winters which cause death of some insects at the preimaginal stages in development, as well as sharp changes in air temperature in the spring-summer period and small areas of breeding places.